When infection hurts: golden rules for managing pediatric skin and soft tissue infections - Giangiacomo Nicolini; Valentina Frasca Polara; Matteo Calvi; Marc García-Lorenzo; Miriam Massese; Gregorio Paolo Milani; Roberta Parrino; Enrico Vidal; Claudia Colomba (Italian Journal of Pediatrics)
Abstract Skin and Soft Tissue Infections (SSTIs) are common in pediatric patients, accounting for nearly 25% of clinical visits. These infections can range from mild to life-threatening and include a severe subset known as Acute Bacterial Skin and Skin Structure Infections (ABSSSI). Prompt diagnosis and appropriate antibiotic use are crucial for optimizing patient outcomes while minimizing adverse effects and antimicrobial resistance. However, empirical treatment often becomes necessary due to the lack of culture specimens, making local epidemiology and clinical presentation key factors in treatment decisions. This expert opinion paper aims to outline the “golden rules” for the management of SSTIs in children, focusing on achieving microbiological clearance, clinical improvement, and effective control of symptoms, such as fever and pain, which significantly impact the child's well-being. These emphasize the principles of antimicrobial stewardship, recommending early diagnosis with appropriate laboratory tests, rational empiric therapy, and prompt switch to targeted therapy based on microbiological findings, as well as proper fever and pain management. The paper also highlights the importance of a multidisciplinary approach for complex cases, optimal dosing, and effective communication with patients' families to improve treatment compliance. Furthermore, antibiotic therapy should be selected to reduce hospital stay and facilitate home-based continuity of care, while follow-up and strengthening of the hospital-territory network are critical for continuity of care after discharge. These recommendations aim to optimize the management of pediatric SSTIs by ensuring comprehensive care from initial diagnosis to post-discharge follow-up, promoting the rational use of antibiotics, and ultimately improving clinical outcomes and quality of life for children and their families.